What is the monetary value of a clean environment in The Himalayas? - Grossman, Victor (2011)
The Himalayas is the world highest mountain system containing famous mountains such as Mt. Everest, Lhotse and K2. Ever since Sir Edmund Hillary and Tenzing Norgay climbed Mt.Everest in 1953 the numbers of tourists has grown over the years, both climbers and regular tourists going for hiking trips and other outdoors activities.